Line 21: Line 21:
 
The first reason why we are using z transform instead of laplace is becuase it is easier to calculate the geometric series by substitution of variable from s to z. Also properties of power series with differential equation is useful.  
 
The first reason why we are using z transform instead of laplace is becuase it is easier to calculate the geometric series by substitution of variable from s to z. Also properties of power series with differential equation is useful.  
  
As the variable <span class="texhtml">''e''<sup>''s''</sup></span> is substituted with z, region of convergence changes from the complex plane. The region of convergence in the complex plane for Z transform is outside region of a unit circle <span class="texhtml"> | ''z'' | = ''r'' = 1</span>, where r is radius of a unit circle.  
+
As the variable <span class="texhtml">''e''<sup>''s''</sup></span> is substituted with z, region of convergence changes from the complex plane. The region of convergence in the complex plane for Z transform is outside region of a unit circle <span class="texhtml">| ''z'' | = ''r'' = 1</span>, where r is radius of a unit circle.  
  
 
Inverse Z transform can be stated as  
 
Inverse Z transform can be stated as  
Line 35: Line 35:
 
  When <math>x[n]=1 (n{\ge}0)</math>
 
  When <math>x[n]=1 (n{\ge}0)</math>
 
   <span class="texhtml">''x''[''n''] = 0(''n'' &lt; 0)</span>
 
   <span class="texhtml">''x''[''n''] = 0(''n'' &lt; 0)</span>
 +
  
<math>X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}1\cdot z^{-n}=\frac{1}{1-z^{-1}}</math>  
+
<math>X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}1\cdot z^{-n}=\frac{1}{1-z^{-1}}</math>&nbsp;, ROC&nbsp;: |z|&gt;1
  
 
== 2. Power series  ==
 
== 2. Power series  ==
  
<math>X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}a^{n} z^{-n}=\frac{1}{1-az^{-1}}</math>  
+
<span class="texhtml">''x''[''n''] = ''a''<sup>''n''</sup></span>
 +
 
 +
<math>X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}a^{n} z^{-n}=\frac{1}{1-az^{-1}}</math> , ROC&nbsp;: |z|&gt;a
  
 
== 3. Exponential funtion  ==
 
== 3. Exponential funtion  ==
 +
 +
<span class="texhtml">''x''[''n''] = ''e''<sup> − ''a''''n''</sup></span>
  
 
<math>X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}e^{-an} z^{-n}=\sum_{n=0}^{\infty}[e^{-a} z^{-1}]^{n}=\frac{1}{1-e^{-a}z^{-n}}</math>  
 
<math>X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}e^{-an} z^{-n}=\sum_{n=0}^{\infty}[e^{-a} z^{-1}]^{n}=\frac{1}{1-e^{-a}z^{-n}}</math>  
  
 
== 4. Sinusoidal function  ==
 
== 4. Sinusoidal function  ==
 +
 +
<span class="texhtml">''x''[''n''] = </span>
  
 
<math>X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}\frac{e^{jn{\omega}} -e^{-jn{\omega}}} {2j} z^{-n}</math> <math> =\frac{1}{2j} (\frac{1}{1-e^{j\omega}z^{-1}}-\frac{1}{1-e^{-j\omega}z^{-1}})</math> <math> =\frac{1}{2j} (\frac{-e^{-j\omega}z^{-1}+e^{j\omega}z^{-1}}{1-e^{-j\omega}z^{-1}-e^{j\omega}z^{-1}+z^{-2}})</math> <math> =\frac{z^{-1}sin(\omega)}{1-2z^{-1}cos(\omega)+z^{-2}}</math>  
 
<math>X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}\frac{e^{jn{\omega}} -e^{-jn{\omega}}} {2j} z^{-n}</math> <math> =\frac{1}{2j} (\frac{1}{1-e^{j\omega}z^{-1}}-\frac{1}{1-e^{-j\omega}z^{-1}})</math> <math> =\frac{1}{2j} (\frac{-e^{-j\omega}z^{-1}+e^{j\omega}z^{-1}}{1-e^{-j\omega}z^{-1}-e^{j\omega}z^{-1}+z^{-2}})</math> <math> =\frac{z^{-1}sin(\omega)}{1-2z^{-1}cos(\omega)+z^{-2}}</math>  
Line 56: Line 63:
 
== 1. Linearity  ==
 
== 1. Linearity  ==
  
<span class="texhtml">''Z''(''a''''x'''''<b>[''n''] + ''b'''''y''[''n'']) = ''a''''X'''''<b>(</b>'''''z'') + ''b''''''''Y''(''z'')</span>  
+
<span class="texhtml">''Z''(''a''''x'''''<b>[''n''] + ''b'''''y''[''n'']) = ''a''''X'''''&lt;b&gt;('''''z'') + ''b''''''''Y''(''z'')'''</b></span>  
  
 
== 2. Time Delay  ==
 
== 2. Time Delay  ==
Line 68: Line 75:
 
== 4. Time Convolution Theorem  ==
 
== 4. Time Convolution Theorem  ==
  
<span class="texhtml">''Z''(''x''[''n''] * ''y''[''n'']) = ''X''(''z'')''Y''(''z'')</span>
+
<span class="texhtml">''Z''(''x''[''n''] * ''y''[''n'']) = ''X''(''z'')''Y''(''z'')</span>  
  
 
----
 
----
  
Comments:
+
Comments:  
 
+
Good job so far. You should specify the ROC for each of the signals that you applied the Z-transform on. -[[User:sbiddand|Sbiddand]]
+
  
 +
Good job so far. You should specify the ROC for each of the signals that you applied the Z-transform on. -[[User:Sbiddand|Sbiddand]]
  
Anybody see anything else? Do you have more questions? Comments? Please feel free to add below.
+
<br>Anybody see anything else? Do you have more questions? Comments? Please feel free to add below.  
  
 
----
 
----
  
[[2010_Fall_ECE_438_Boutin|Back to ECE438, Fall 2010, Prof. Boutin]]
+
[[2010 Fall ECE 438 Boutin|Back to ECE438, Fall 2010, Prof. Boutin]]

Revision as of 18:58, 16 December 2010

Z transform


Z transform is a general form of DTFT. If x[n] is a discrete periodic funtion, DFT of this function is $ x[k] = \sum_{n=0}^{N-1} x[n]e^{-j\frac{{2\pi}k n}{N}} $

Let's say x[n] is discrete nonperiodic function. Nonperiodic function is also a function with period $ \infty $. Therefore DTFT of this function can be DFT with $ N=\infty $. $ \lim_{N\to\infty}\sum_{n=0}^{N-1}x[n]e^{-j\frac{{2\pi}k n}{N}}=\sum_{n=0}^{\infty}x[n]e^{-j{\omega}n} $, where $ \omega=\lim_{N\to\infty}\frac{{2\pi}k}{N} $

$ X(w)=\sum_{n=0}^{\infty}x[n]e^{-j{\omega}n} $ ---> DTFT

The difference between DFT and DTFT is that DFT has a discrete function with k and DTFT is a continuous function with ω.

Let's generalize the DTFT. By substitution of real value frequency ω into complex frequency value s = σ + iω, DTFT is now discrete function of Laplace transform.

$ X(s)=\sum_{n=0}^{\infty}x[n]e^{-sn} $ ---> Laplace Transform

When es = z, it is a Z transform.

$ X(z)=Z[x[n]]=\sum_{n=0}^{\infty}x[n]z^{-n} $ ---> Z Transform

The first reason why we are using z transform instead of laplace is becuase it is easier to calculate the geometric series by substitution of variable from s to z. Also properties of power series with differential equation is useful.

As the variable es is substituted with z, region of convergence changes from the complex plane. The region of convergence in the complex plane for Z transform is outside region of a unit circle | z | = r = 1, where r is radius of a unit circle.

Inverse Z transform can be stated as

$ x[n]=\frac{1}{j{2\pi}}\oint{X(z)z^{n-1}dz} $

These are the examples of Z transform.


1. Unit step

When $ x[n]=1 (n{\ge}0) $
  x[n] = 0(n < 0)

$ X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}1\cdot z^{-n}=\frac{1}{1-z^{-1}} $ , ROC : |z|>1

2. Power series

x[n] = an

$ X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}a^{n} z^{-n}=\frac{1}{1-az^{-1}} $ , ROC : |z|>a

3. Exponential funtion

x[n] = ea'n

$ X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}e^{-an} z^{-n}=\sum_{n=0}^{\infty}[e^{-a} z^{-1}]^{n}=\frac{1}{1-e^{-a}z^{-n}} $

4. Sinusoidal function

x[n] =

$ X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}\frac{e^{jn{\omega}} -e^{-jn{\omega}}} {2j} z^{-n} $ $ =\frac{1}{2j} (\frac{1}{1-e^{j\omega}z^{-1}}-\frac{1}{1-e^{-j\omega}z^{-1}}) $ $ =\frac{1}{2j} (\frac{-e^{-j\omega}z^{-1}+e^{j\omega}z^{-1}}{1-e^{-j\omega}z^{-1}-e^{j\omega}z^{-1}+z^{-2}}) $ $ =\frac{z^{-1}sin(\omega)}{1-2z^{-1}cos(\omega)+z^{-2}} $


Properties of Z transform

1. Linearity

Z(a'x[n] + by[n]) = a'X<b>(z) + b'''Y(z)

2. Time Delay

$ Z(x[n-k])=z^{-k}[X(z)+\sum_{n=1}^{k}x[-n]z^{n}] $

3. Time Advance

$ Z(x[n+k])=z^{k}[X(z)-\sum_{n=0}^{k-1}x[n]z^{-n}] $

4. Time Convolution Theorem

Z(x[n] * y[n]) = X(z)Y(z)


Comments:

Good job so far. You should specify the ROC for each of the signals that you applied the Z-transform on. -Sbiddand


Anybody see anything else? Do you have more questions? Comments? Please feel free to add below.


Back to ECE438, Fall 2010, Prof. Boutin

Alumni Liaison

Questions/answers with a recent ECE grad

Ryne Rayburn